Bone turnover in non-steroid treated rheumatoid arthritis. Issue 3 (March 1994) - Compston, J E; Vedi, S; Croucher, P I; Garrahan, N J; O'Sullivan, M M
Abstract : OBJECTIVE--To examine whether changes in cancellous bone turnover and resorption cavity depth contribute to bone loss in patients with non-steroid treated rheumatoid arthritis. METHODS--Iliac crest biopsies were obtained from 37 patients with non-steroid treated rheumatoid arthritis, 13 male and 24 female, aged 37-71 years. Bone turnover and resorption cavity characteristics were quantitatively assessed using semiautomated computerised techniques. RESULTS--When compared with age- and sex-matched control values, there was a significant reduction in bone formation rate at tissue level and activation frequency (P < 0.001) in the patient group. The eroded perimeter, mean and maximum eroded depth and cavity area were also significantly reduced (P < 0.01, < 0.005, < 0.01 and < 0.005 respectively). CONCLUSION--These results demonstrate low bone turnover in non-steroid treated rheumatoid arthritis and indicate that the reduced bone mass in these patients is due mainly to a negative remodelling balance.